2022
DOI: 10.3390/nu14194183
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Peptides Extracted from Deer Antler

Abstract: Deer antler is widely used as a nutraceutical in Asian countries. In the past decades, deer antler peptides (DAPs) have received considerable attention because of their various biological properties such as antioxidant, anti-inflammatory, anti-bone damage, anti-neurological disease, anti-tumor and immunomodulatory properties. This review describes the production methods of DAPs and the recent progress of research on DAPs, focusing on the physiological functions and their regulatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…Many studies have shown that antlers are rich in active ingredients, which can replenish blood, invigorate energy and improve sexual function [ 6 , 7 ]. They are very rich in peptides and proteins which are considered to be important components for promoting tissue repair, antioxidant production and neuroprotection [ 8 ]. Antler polysaccharide, one of the important components of antler, is believed to prevent osteoporosis and enhance immunity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that antlers are rich in active ingredients, which can replenish blood, invigorate energy and improve sexual function [ 6 , 7 ]. They are very rich in peptides and proteins which are considered to be important components for promoting tissue repair, antioxidant production and neuroprotection [ 8 ]. Antler polysaccharide, one of the important components of antler, is believed to prevent osteoporosis and enhance immunity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies reported certain mechanism such as the hydrolyzed deer polypeptides and polypeptides in velvet horns prevented oxidative stress and cell death by regulating the Bax/BBC-2 ratio [ 103 , 106 ]. Xia et al [ 107 ] suggested that peptides extracted from deer antler can manifest a neuroprotective ability, with a positive effect on neurological diseases through their anti-inflammatory activity and antioxidant properties. The human body is capable of producing only nine amino acids (histidine, isoleucine, leucine, lysine, methionine, threonine, tryptophan, phenylalanine, valine) of the 22 amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…PAP effectively inhibits bone resorption through its antiinflammatory and antioxidative effects. PAP displays the capability to diminish bone resorption by mitigating inflammation, which accomplishes this by reducing the levels of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1 (IL-1), and interleukin-6 (IL-6), (44)(45)(46). By doing so, it curtails the inflammatory…”
Section: Inhibition Of Bone Resorptionmentioning
confidence: 99%
“…response, safeguarding osteoblasts, and thwarting the induction of bone resorption prompted by pro-inflammatory cytokines (44)(45)(46). Furthermore, PAP exerts an antioxidative effect that contributes to the inhibition of bone resorption.…”
Section: Inhibition Of Bone Resorptionmentioning
confidence: 99%